Simulation and practice: a repeated measurements perspective - Leppink, Jimmie; Maestre, José Maria; Rojo Santos, Elena; del Moral, Ignacio (Spanish Journal of Medical Education, 2021)
Simulation can provide powerful opportunities for the development of essential skills in a safe environment that has no consequences for patients. However, to understand the effects of simulation on clinical practice, we need a design that allows us to systematically measure one or more variables of interest repeatedly during and after the simulation and where possible also before the simulation. Although this kind of research is often associated with larger samples of participants, through a simulated example this article demonstrates that this type of design can be used even in settings where there is only one participant. An increased use of this kind of design may help us to understand the effects of simulation on practice on the short and long term and how these effects may depend on the context in which simulation takes place.